Ben Franklin of old Philadelphia; illus. by Fritz Eichenberg. - Cousins, Margaret; Eichenberg, Fritz, illus (Random House, New York, 1952)
A biography of the American who became known for his work as a printer, author, inventor, and statesman.
Keywords: Franklin, Benjamin, -- 1706-1790.